The Effect of 5wt.% and 10wt.% Salacca Frond Fiber Addition on Kevlar and Carbon Fiber Reinforced Epoxy using Vacuum Assisted Resin Transfer Molding (VARTM) Method for Bulletproof Vest Application - Vina Nanda Garjati; Vika Rizkia; Nur Agnes Aggraeni; Muslimin (Recent in Engineering Science and Technology, 2023)
Bulletproof vests as self-protection for military personnel are generally made from synthetic fiber-reinforced composites. Kevlar and carbon fiber reinforced composites have been able to withstand bullet penetration rates and have lightweight characteristics, but production costs with synthetic fibers are relatively expensive. The use of substitute materials from natural fiber is very potential, due to the abundance of natural fiber, lightweight, and relatively cheap price. One of the potential natural fibers is fiber from the salacca midrib. This study focused on the effect of adding salacca frond fiber on the composite characteristics of Kevlar fiber and carbon fiber, with SiC and Al2O3 fillers. The manufacture of this composite is carried out by the Vacuum Assisted Resin Transfer Molding (VARTM) method. There are 4 variations of fiber volume fractions and fillers as reinforcement added to this composite. From the results of observations with SEM, the results of the matrix and reinforcement are well bound. The ballistic test results show that all variations of test samples can withstand the bullet rate so that it does not penetrate. The results of mechanical tests show that currently the addition of salacca frond fiber has not significantly improved the mechanical properties of the composite